COST REDUCTION STRATEGY IN PAPAYA PRODUCTION: IMPLEMENTING DMAIC AND LEAN FARM - Parcelino Prabowo, Rommy; Yudoko, Gatot (CV. Radja Publika, 2025)
Great Giant Pineapple (GGP) faced significant losses in papaya production in 2022, with actual costs reaching IDR 25,000/Kg against a budget of IDR 5,900/Kg, resulting in a IDR 4.2 billion loss. Plant care and maintenance, particularly fertilization and manual pesticide application, were the primary cost drivers. Utilizing the DMAIC methodology and SAP data, the research focused on cost reduction. Fertilization costs were dominated by materials, which were deemed unchangeable due to research-backed recommendations. Therefore, the study targeted labor efficiency in manual pesticide application. Cost-benefit analysis identified